Digital Economy and Tourism marketing: A Systematic Literature Review of Strategies, Challenges, and Opportunities - Sri Iswati; Diky Budiman; Sakum Sakum (Jurnal Bisnis dan Pemasaran Digital, 2026)
Purpose: This study aims to systematically examine the relationship between the digital economy and tourism marketing by identifying dominant digital strategies, implementation challenges, and emerging opportunities in tourism industries. Research Methodology: This study employed a Systematic Literature Review (SLR) approach using the PRISMA protocol. Scientific articles published between 2021 and 2026 were collected from Google Scholar, ScienceDirect, Springer Nature Link, and ResearchGate. The review process included identification, screening, eligibility, and inclusion stages using keywords related to digital economy, tourism marketing, digital marketing, and tourism technology. Results: The findings indicate that the digital economy has fundamentally transformed tourism marketing from conventional promotion into integrated digital ecosystems characterized by AI-based personalization, smart tourism systems, digital storytelling, social media engagement, immersive tourism experiences, digital finance, and data-driven marketing strategies. The review also identified major challenges, including digital infrastructure gaps, low digital literacy, platform dependency, sustainability issues, and organizational capability limitations. Furthermore, the digital economy creates opportunities for sustainable tourism development, customer experience enhancement, tourism innovation, and global tourism market expansion. Conclusions: Tourism marketing in the digital economy era requires integrated strategies combining technological innovation, organizational agility, digital literacy, sustainability orientation, and customer-centered experiences. Limitations: This study relied only on secondary data from scientific literature and did not include empirical validation through primary data collection. Contributions: This study contributes theoretically by providing a comprehensive conceptual mapping of digital economy implementation in tourism marketing and by offering insights for tourism practitioners, SMEs, destination managers, and policymakers.